THE EKSISTENSI PEREMPUAN DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO BERDASARKAN FEMINISME EKSISTENSIALIS SIMONE DE BEAUVOIR - Diah Anggraini (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
This study aims to describe the forms of marginalization as the others and forms of resistance as a form of existence in Dian Purnomo's novel Women Crying for Black Moon based on Simone de Beauvoir's Existentialist Feminism approach. The data for this study are sentences that express forms of marginalization as others and forms of resistance as a form of existence in the novel Woman Crying for the Black Moon by Dian Purnomo, which will be published by Gramedia Pustaka in 2021. Data collection was carried out using reading, note-taking and writing techniques. data corpus. The research data were analyzed using Simone de Beauvoir's existentialist feminist theory. The results of the study found that the forms of marginalization as others in the novel Woman Crying for the Black Moon by Dian Purnomo contained nineteen data describing forms of marginalization as Others in the novel Woman Crying for the Black Moon by Dian Purnomo, There were sixteen data found as data describing forms of resistance as a form of existence in Dian Purnomo's novel Women Crying for the Black Moon. Magi's attitude shows that a woman is actually not immediately used as an object of oppression but can become someone who is able to think, define and act so that one day she can determine her future well and of course can become a woman who exists.Keywords: women, marginalization, existence